Modified multi-prime RSA using discriminant of a quadratic and Chinese remainder theorem / Nur Fatimah Kabulanto and Farah Aina Abdul Razak - Kabulanto, Nur Fatimah; Abdul Razak, Farah Aina (2018)
RSA is one public key Cryptosystem to secure information and communication from third parties and it can be factor by user authentication. In order to achieving security from unwanted users, the message will encode to make it unreadable format. RSA Cryptosystem is generally utilized in the popular implementation of public key Cryptosystem. In RSA Cryptosystem there are two completely different keys are generated, one key's utilized in encryption data and other corresponding key's utilized for decryption data. Many innovative ideas for RSA Cryptosystem have been presented for the past two decades, and many corresponding problems remain to be resolved. Therefore, in this study we introduce a modified RSA Cryptosystem using a hybrid of discriminant quadratic and Chinese Remainder Theorem. The securities of these models are based on the difficulties of solving multiple hard problems simultaneously. The newly algorithm will not only increase the security of system but also has high correct ability. Therefore, we implied this new formula to improve the weakness of RSA Cryptosystem in decryption and make the security of system to be more advanced.